Public speaking as a tool for teaching theoretical English language disciplines in universities of Uzbekistan - Porsayeva, Malika Makhmudovna (The Lingua Spectrum, 2026)
This article examines the role of Public Speaking techniques in teaching theoretical English language disciplines at universities in Uzbekistan. The study explores how rhetorical and communicative strategies may improve student engagement, comprehension of theoretical material, and academic speaking competence during lecture-based instruction. Particular attention is devoted to the integration of Public Speaking elements such as speech organization, voice modulation, rhetorical questioning, audience interaction, storytelling, and non-verbal communication into subjects including Stylistics, Lexicology, Analytical Reading, and Theoretical Grammar. The research is based on classroom observations, interactive lecture practices, and student feedback analysis conducted within English language departments of higher educational institutions. The findings demonstrate that the use of Public Speaking techniques contributes to the transformation of traditional lectures into more interactive and student-centered learning environments. The study concludes that integrating communicative and rhetorical methods into theoretical instruction may significantly enhance the effectiveness of English language teaching in modern higher education. In addition, the article emphasizes the importance of developing students’ critical thinking, confidence, and presentation skills through communicative academic practices, which may further support future professional activities of English language specialists, teachers, translators, and researchers in contemporary educational settings.